Navigating the Halal Traceability in Global Supply Chains: Deep Insights from Small-Scale Food Producers - Aan Zulyanto; Dharma Setiawan (Future Techno-Science, 2025)
The global halal food industry has experienced rapid expansion, driven by growing Muslim populations and increasing consumer demand for certified halal products. Despite this growth, small-scale food producers continue to face significant challenges in implementing effective halal traceability systems within complex global supply chains. This study investigates the traceability challenges encountered by small-scale food producers in Indonesia, with broader implications for the global halal food sector. Employing a qualitative research design, data were collected through in-depth semi-structured interviews with fifteen small-scale halal food producers in Bengkulu Province, Indonesia. Thematic analysis was applied to identify key patterns and themes from the data. The findings reveal four major themes: (1) systemic traceability challenges related to documentation and supply chain visibility; (2) difficulties in accessing and maintaining halal certification; (3) limited adoption of digital technologies for traceability management; and (4) trust and integrity issues across the supply chain. This study concludes that targeted policy interventions, technology capacity-building programs, and streamlined certification processes are essential to support small-scale producers in achieving robust halal traceability. The findings contribute to the growing body of halal supply chain literature and offer practical implications for industry stakeholders and policymakers.